Tingkat Indeks Kepuasan Masyarakat Terhadap Kualitas Pelayanan Publik Surat Keterangan Catatan Kepolisian (SKCK) Di Polres Payakumbuh - Ario Harisman; Khairul Khairul (Jurnal Mirai Management, 2023)
This research employed a quantitative descriptive method to obtain a true picture of the assessment of the performance of the Public Service for Police Record Certificate (SKCK) at Polres Payakumbuh. The objective of this study was to understand and determine the level of community satisfaction with the SKCK services in the Polres Payakumbuh area. The population of this study was the individuals who utilized the SKCK services at Polres Payakumbuh, totaling 100 respondents. A sample of 50 respondents was taken from the population using simple random sampling technique. Data collected from the survey on community satisfaction with the SKCK services at Polres Payakumbuh were analyzed using the SPSS (Statistical Package for the Social Sciences) software. The SPSS facilitated the data analysis process by providing comprehensive statistical features. Based on the analysis, it can be concluded that the community's level of satisfaction with the quality of public service for the SKCK at Polres Payakumbuh obtained a performance index value of 81.18, falling under the category of "GOOD." The research showed that all nine elements of community satisfaction were fulfilled in the SKCK service, meeting the prevailing regulations and guidelines. The study suggests continuous efforts to improve the quality of services by providing consistent training for the front-line staff in Service Excellence, simplifying the Standard Operating Procedure (SOP) for service delivery, establishing a dedicated team to handle complaints and feedback, enhancing the competencies of service providers, recognizing and motivating high-performing employees, and considering incentives for staff's well-being. Regularly conducting surveys and using the Index of Customer Satisfaction (IKM) as a benchmark for service quality will help maintain the public service's standard and identify any necessary improvements in the future.